The Effect of Think Pairs Share (TPS) Method on Learning Outcomes of Grade 2 Multiplication Materials at Elementary School: Pengaruh Metode Think Pairs Share (TPS) Terhadap Hasil Belajar Materi Perkalian Kelas 2 SD - Prasihly Innie; Nur Efendi (Academia Open, 2022)
The purpose of this study was to determine the use of the Think Pairs Share Method to increase student participation in understanding Mathematical Multiplication material in elementary schools. The method used in this research is a quantitative research approach. This study used the One Group Pretest Posttest design. The population used in this study were all students of class II SDN Kedinding with a sample of 22 students. Data collection techniques in this study used learning outcomes tests, where there are pretest (initial test) and postest (final test). The results of this study obtained the value of the Eta Square test with a value of 0.5582 indicating that there was a great influence with the Think Pairs Share Method on the learning outcomes of Class II Multiplication Material at SDN Kedinding, Tarik District.